Pendampingan Implementasi Odoo untuk Pengelolaan E-Commerce Berbasis Entrepreneurship pada UMKM - Aggi Panigoro Sarifiyono; Ratih Hadiantini; Fitriyani; Kurnia (Ma'soem University, 2026)
Digital transformation has become an essential requirement for Micro, Small, and Medium Enterprises (MSMEs) to remain competitive in the rapidly evolving digital economy. However, many MSMEs still face challenges in managing their business operations, such as manual financial recording, inventory management, and limited utilization of digital marketing tools. Therefore, this community service program aims to enhance the digital entrepreneurship capacity of MSMEs through the implementation of the Odoo application as an integrated e-commerce and business management platform. The partners involved in this program are several MSMEs located in Sukapura and Bojongloa Kidul, Bandung City, operating in sectors such as culinary businesses, fashion, boarding house services, and agricultural products. The methods applied in this program include needs assessment, training on the use of the Odoo application, assistance in developing e-commerce websites, and evaluation of system utilization in the partners’ business operations. The results show that the implementation of Odoo successfully helped MSMEs develop e-commerce websites, display digital product catalogs, and improve business information management as well as communication with customers. In addition, this activity improved the digital literacy of MSME partners and provided practical learning experiences for students in implementing business technology. These findings indicate that the use of Odoo-based ERP technology can serve as a strategic solution to support the digital transformation of MSMEs, thereby improving business professionalism and expanding market reach sustainably.